Pro-tumoral Effects of Intra-tumoral Neutrophils in the Glioblastoma Microenvironment. (1st September 2019) - Shah, Sumedh S; Yagnik, Garima; Nguyen, Alan T; Wadhwa, Harsh; Spatz, Jordan; Safaee, Michael; Cheng, Justin; Aghi, Manish K
Abstract: INTRODUCTION: The glioblastoma microenvironment contains immune cells, particularly well-defined macrophage populations; however, intratumoral neutrophils and their effects on GBM biology are under-characterized. While tumor-associated neutrophils (TANs) were initially thought as passive bystanders due to their short-lived nature, current investigation of TANs in other cancer types revealed distinct pro-tumoral roles. Therefore, we sought to characterize TANs in the glioblastoma microenvironment and define their oncologic effects. METHODS: Following informed consent, patient-derived GBM samples were collected for flow cytometry of TANs, which were then used to produce conditioned media (CM) for in Vitro studies on tumor cell proliferation and ELISA quantification of TAN-secreted factors. Single-cell RNA sequencing was performed on TANs to identify pro-tumoral factors. RESULTS: Flow cytometric analysis (CD11b+/CD15+ /CD66b+) indicated higher percentages of TAN-infiltration to glioblastoma compared to low-grade gliomas (1.76% [n = 13] vs 0.33% [n = 6], P = .03). Using the Transwell migration assay with glioblastoma tumor CM, we found recruitment of circulating neutrophils to tumor sites is mediated by leukotriene-B4 and that this chemoattraction can be blocked with an LtB4 receptor antagonist, LY293111. We then performed single-cell RNA sequencing of isolated TANs and identified upregulation of osteopontin. Osteopontin is linked to GBM stem cell-like phenotype maintenance, thus, we decided to investigate osteopontin as a possible driver of pro-tumoral signaling. Osteopontin concentration was significantly higher in TAN CM than in patient-matched peripheral blood neutrophil CM (3.2 ng/mL [n = 3] vs 0.02 ng/mL [n = 3], P < .05). In Vitro, TAN CM led to significantly increased GBM cell proliferation and increased stem marker expression (Nanog, Oct4, Sox2) when incubated with neurospheres from an established GBM line. Pro-tumoral effects were lost in presence of osteopontin-neutralizing antibodies. CONCLUSION: This study elucidates a possible mechanism of neutrophil-mediated pro-tumoral signaling. We found that neutrophils are recruited to tumor sites and play a biologically relevant role in GBM cellular proliferation and maintenance of a stem cell phenotype via osteopontin secretion.